Separation Hydrometallurgy of Rare Earth Elements - Zhang, Jack.; Zhao, Baodong; Schreiner, Bryan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes in a comprehensive manner the technical aspects of separation of rare earth elements into individual elements for industrial and commercial use. The authors include details on and differentiate among the effective separation of rare earth elements for various parts of the world. They introduce new applications of separation of rare earth elements from concentrates of diverse ore types.
Rare Earth Elements and Minerals -- Earth Ore Concentrating, Decomposition and Leaching -- Rare Earth Element Separation Technologies -- Principals of Solvent Extraction Separation of Rare Earth Elements -- Equipment for Rare Earth Solvent Extraction Separation -- Rare Earth Solvent Extraction Separation Processes -- Rare Earth Element Waste Management and Environment Protection -- Future Developments in Rare Earth Element Separation.
Keywords: Materials -- Analysis; Manufactures; Geology; Characterization and Analytical Technique; Machines, Tools, Processes; Geology